2021
DOI: 10.1186/s12872-021-02244-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and in-hospital mortality of postoperative hyperlactatemia in patients after acute type A aortic dissection surgery

Abstract: Background Hyperlactatemia may be caused by increased production due to tissue hypoxia or non-hypoxia. The aim of this study was first to identify risk factors for postoperative hyperlactatemia (POHL) after Stanford type A acute aortic dissection surgery (AADS) and construct a predictive model, and second to evaluate the impact of POHL on prognosis. Methods This retrospective study involved patients undergoing AADS from January 2016 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
1
19
0
2
Order By: Relevance
“…This correlation has been assessed by different studies, but variability remains regarding the timing of measurement of lactate in the postoperative period. Lactate levels were not a predictor of mortality when measured on admission to ICU but a positive correlation was observed when the measurement was carried out at 6 h and within 12 h of return to ICU 6 . Measuring the lactate level after a few hours in the ICU may be more logical and this is the area where the study by Gemelli et al 1 is especially valuable.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…This correlation has been assessed by different studies, but variability remains regarding the timing of measurement of lactate in the postoperative period. Lactate levels were not a predictor of mortality when measured on admission to ICU but a positive correlation was observed when the measurement was carried out at 6 h and within 12 h of return to ICU 6 . Measuring the lactate level after a few hours in the ICU may be more logical and this is the area where the study by Gemelli et al 1 is especially valuable.…”
mentioning
confidence: 97%
“…Apart from these three studies, where the correlation between lactate levels and the outcome was reported extensively, there are also other studies that used lactate levels as one of the parameters for determining outcome. These studies also had significant variations for defining “high lactate” and the values ranged from 3 to 6 mmol/L 4–6 …”
mentioning
confidence: 99%
See 3 more Smart Citations